2015
DOI: 10.7318/kjfc/2015.30.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Food Habits and Eating Behavior of Children with Obesity and/or Precocious Puberty by Nutrition Education Monitoring

Abstract: The purpose of this study was to investigate improvement of food habits and eating behavior in children with obesity and precocious puberty by nutritional education monitoring. The results are as follows. Average height and weight of subjects exceeded Korean height and weight standards for children as outlined by The Korea Pediatric Society. Using nutrition education monitoring, meals became more regular, overeating significantly decreased, and eating speed decreased. Further, frequencies of eating-out and nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Pearson et al [33] found that students who reported a high frequency of eating snacks and fast foods exhibited low consumption of fruits and vegetables, and the consumption of such foods affected their intake at regular meals. Recently, nutrition problems have emerged among Korean children as a result of increased intake of high-calorie, low-nutrient foods, high volumes of sugars, and excessive consumption of ingredients such as caffeine and food additives [34,35]. Because children's eating behavior is affected by family environmental variables, eating habits that contribute to their parents' obesity and disease-inducing behaviors may also be related.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson et al [33] found that students who reported a high frequency of eating snacks and fast foods exhibited low consumption of fruits and vegetables, and the consumption of such foods affected their intake at regular meals. Recently, nutrition problems have emerged among Korean children as a result of increased intake of high-calorie, low-nutrient foods, high volumes of sugars, and excessive consumption of ingredients such as caffeine and food additives [34,35]. Because children's eating behavior is affected by family environmental variables, eating habits that contribute to their parents' obesity and disease-inducing behaviors may also be related.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary attitudes and habits benefit from greater nutritional knowledge. Therefore, it is very important to identify and correct the effects of dietary habits on the obesity index [ 16 ]. This study categorized dietary habits into WG and WL groups in accordance with obesity index, and focused on means of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rise in precocious puberty is believed to be due to factors such as environmental pollution from industrialization, obesity resulting from dietary changes like increased consumption of instant or fast food, pituitary gland hyperfunction caused by television or smartphone use, and a family history of early puberty. Regarding obesity, the increase in endocrine disruptors, which are similar to female hormones, and the secretion of female hormones from fat cells are thought to have a particularly significant impact on girls [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These agents have the effect of desensitizing the gonadotropin cells in the pituitary gland to endogenous GnRH stimulation. Typically, this treatment is applied for a period of 2 to 5 years, and is usually discontinued around the age of 11 years for girls and 12 years for boys [4,9]. The use of traditional Asian medicine in the treatment and management of precocious puberty has recently gained traction, leading to an increase in treatment rates [10,11].…”
Section: Introductionmentioning
confidence: 99%